1994
DOI: 10.1177/019459989411000303
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of surgical treatments for squamous cell carcinoma of the temporal bone: A literature review

Abstract: A review of all publications dealing with surgical treatment for squamous cell carcinomas of the temporal bone was performed. No randomized or nonrandomized control studies were identified. All studies were case series without control subjects. Twenty-six of 96 publications, which contained information on 144 patients, were analyzed. Several inferences are suggested by the available evidence; however, these areas should be investigated by properly designed randomized clinical trials: (1) patients with carcinom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
21
0
2

Year Published

1997
1997
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(27 citation statements)
references
References 81 publications
2
21
0
2
Order By: Relevance
“…The extant literature consists of numerous case series that have reported a wide range of survival data, reflecting differences in the underlying characteristics of cohorts drawn from various institutions. 1,6,[8][9][10][12][13][14][15]18,19,22,24,[30][31][32][33][34][35][36][37][38][39][40][41] Historical survival data can be most readily generalized to clinical practice if factors predictive of outcome can be identified. Several larger series have reported preliminary descriptions of factors influencing survival, based on univariate comparisons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extant literature consists of numerous case series that have reported a wide range of survival data, reflecting differences in the underlying characteristics of cohorts drawn from various institutions. 1,6,[8][9][10][12][13][14][15]18,19,22,24,[30][31][32][33][34][35][36][37][38][39][40][41] Historical survival data can be most readily generalized to clinical practice if factors predictive of outcome can be identified. Several larger series have reported preliminary descriptions of factors influencing survival, based on univariate comparisons.…”
Section: Discussionmentioning
confidence: 99%
“…These numbers are reflections of the underlying characteristics of the patient cohort at each institution. [8][9][10][11][12][13][14][15][17][18][19]22,23,[30][31][32]34,35,[37][38][39][40][41][42] Attempting to improve understanding of prognostic factors, 5 groups have recently analyzed outcomes using univariate analyses. In 1997, Testa et al 20 Based on these outcomes data, we currently consider the minimum operation for the vast majority of malignant disease involving the external auditory canal/temporal bone to be a lateral temporal bone resection.…”
Section: Discussionmentioning
confidence: 99%
“…1) However, whether aggressive resection helps to prolong survival significantly remains unclear. 13) In our previous series of 15 patients who underwent anterolateral cavernous sinus excision, the 5-year disease-free survival rate was 0%. 5) Therefore, we considered that malignant tumors requiring anterolateral cavernous sinus excision contraindicate surgery, and stereotactic radiotherapy and chemotherapy should take precedence in such patients.…”
Section: Discussionmentioning
confidence: 92%
“…A retrospective review including 144 patients did not find evidence of improved survival with the addition of RT to TBR (with 48 vs. 44.4% 5-year survival for TBR + RT vs. TBR alone, respectively) [34]. Wang [25] reported that Adjuvant postoperative RT was not significantly correlated with the overall survival rates but it is unnecessary for early stage EAC SCC, particularly in patients with guaranteed intraoperative tumor-free margins.…”
Section: Discussionmentioning
confidence: 99%